2016
DOI: 10.1002/osp4.59
|View full text |Cite
|
Sign up to set email alerts
|

Portion‐size preference as a function of individuals' body mass index

Abstract: SummaryObjectiveLarge portions of food are often blamed for rising rates of obesity. We tested the possibility that people who are heavier may tend to select or prefer larger portions than do people who are lighter.MethodsParticipants (total N = 798) were asked to choose between a small and larger portion of pasta for a hypothetical meal (Studies 1, 2 and 4), to indicate their ideal portion from a range of portion‐size options (Study 2), or to select their preferred portion size from each of 28 portion pairs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Despite the estimation raising with increasing BMI, BMI did not affect normal portion sizes statistically significantly. Previous studies show contradictory results ( Dodd et al, 1976 ; Burger et al, 2007 ; Brunstrom et al, 2008 ; Lewis et al, 2015 ; Reily et al, 2016 ; Embling et al, 2021 ). Likely, the presentation style and type depicted foods play a role in the outcomes as the study from Burger et al (2007) reported a positive relationship between BMI and some of the foods tested (peanuts, M&M candies, cereals, jam, and soda), but also some foods with a negative relationship (margarine and apple sauce) and some with no differences (rice, chips, peanut butter, macaroni and cheese, and water).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Despite the estimation raising with increasing BMI, BMI did not affect normal portion sizes statistically significantly. Previous studies show contradictory results ( Dodd et al, 1976 ; Burger et al, 2007 ; Brunstrom et al, 2008 ; Lewis et al, 2015 ; Reily et al, 2016 ; Embling et al, 2021 ). Likely, the presentation style and type depicted foods play a role in the outcomes as the study from Burger et al (2007) reported a positive relationship between BMI and some of the foods tested (peanuts, M&M candies, cereals, jam, and soda), but also some foods with a negative relationship (margarine and apple sauce) and some with no differences (rice, chips, peanut butter, macaroni and cheese, and water).…”
Section: Discussionmentioning
confidence: 84%
“…However, other reports with a similar design found no difference as a function of BMI ( Brunstrom et al, 2008 ; Embling et al, 2021 ). In studies allowing the choice between fixed portion sizes, some indicated that participants with obesity order larger portions than non-obese ( Dodd et al, 1976 ) which was not confirmed by other reports ( Reily et al, 2016 ). Thus, the issue of the relation between BMI and portion size is controversial and remains unresolved.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation